The effect of gluten free diet on markers of celiac disease and association with behavioral symptoms in children diagnosed with Autism Spectrum Disorders - Ghalichi, Faezeh; Ostadrahimi, Alireza; Malek, Ayyoub; Ghaemmaghami, Jamal (Progress in Nutrition, 2016)
Purpose: The objectives of this study were to measure markers of celiac disease before and after implementing a gluten free diet and also evaluating its association with autism severity. Methods: The present randomized clinical trial was accomplished over 80 subjects diagnosed with Autism Spectrum Disorders (ASD) by the Autism Diagnostic Interview-Revised (ADI-R). Participants were randomly divided into Gluten Free Diet (GFD) and regular diet groups for 6 weeks. Immunological markers consisting of IgA, tTGIgA, tTGIgG and EMAIgG were measured. Findings: In this study, 6 patients were tTGIgA positive. In the GFD group, tTGIgA decreased insignificantly (from 3.62 ± 4.25 to 3.41 ± 3.51 U/ml; P<0.05) while it increased significantly (from 2.80 ± 3.54 to 3.96 ± 4.10 U/ml; P<0.05) in the regular diet group. Conclusion: These results suggest an underlying immune reactivity to gluten in a subset of children with ASD; however, celiac disease (CD) was not detected in any of the cases. Further investigations are necessary to clarify the possible relationship between ASD and celiac disease. Iranian Registry of Clinical Trials (IRCT201404212017N20), http://www.irct.ir